-6x - 2 = (3x + 1)^2

Question

Asked 2/27/2013 9:58:27 PM

Updated 9/21/2014 12:19:25 PM

1 Answer/Comment

This conversation has been flagged as incorrect.

Edited by andrewpallarca [9/21/2014 12:15:36 PM], Flagged by andrewpallarca [9/21/2014 12:15:38 PM]

s

samn|Points 3831|

Question

Asked 2/27/2013 9:58:27 PM

Updated 9/21/2014 12:19:25 PM

1 Answer/Comment

This conversation has been flagged as incorrect.

Edited by andrewpallarca [9/21/2014 12:15:36 PM], Flagged by andrewpallarca [9/21/2014 12:15:38 PM]

Rating

3

-6x - 2 = (3x + 1)^2;

-6x - 2 = 9x^2 + 6x + 1;

9x^2 + 6x + 1 = -6x - 2;

9x^2 + 6x + 6x + 1 + 2 = 0;

9x^2 + 12x + 3 = 0;

3(3x + 1)(x + 1) = 0;

3(3x + 1) = 0;

9x + 3 = 0; 9x = -3; x = -3/9; x = -1/3;

x + 1 = 0; x = -1

The solution is: x = -1/3, x = -1

-6x - 2 = 9x^2 + 6x + 1;

9x^2 + 6x + 1 = -6x - 2;

9x^2 + 6x + 6x + 1 + 2 = 0;

9x^2 + 12x + 3 = 0;

3(3x + 1)(x + 1) = 0;

3(3x + 1) = 0;

9x + 3 = 0; 9x = -3; x = -3/9; x = -1/3;

x + 1 = 0; x = -1

The solution is: x = -1/3, x = -1

Added 9/21/2014 12:19:25 PM

This answer has been confirmed as correct and helpful.

31,908,926

questions answered

There are no comments.